2013
DOI: 10.1097/hjh.0b013e32835b50aa
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and renoprotective actions of soluble epoxide hydrolase inhibition in ANG II-dependent malignant hypertension are abolished by pretreatment with L-NAME

Abstract: Objective The present study was performed to investigate in a model of malignant hypertension if the antihypertensive actions of soluble epoxide hydrolase (sEH) inhibition are nitric oxide (NO)-dependent. Methods ANG II-dependent malignant hypertension was induced through dietary administration for 3 days of the natural xenobiotic indole-3-carbinol (I3C) in Cyp1a1-Ren-2 transgenic rats. Blood pressure (BP) was monitored by radiotelemetry and treatment with the sEH inhibitor [cis-4-[4-(3-adamantan-1-yl-ureido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Using the same model, we recently showed that development of typical malignant hypertension is not simply the result of RAS overactivity, but also of its perturbed interactions with other vasoactive systems. In particular, we found that the development of ANG II-dependent malignant hypertension in Cyp1a1-Ren-2 transgenic rats is accompanied by decreased intrarenal EET concentrations [26,38,41]. Based on the above considerations, we first decided to employ the model in an attempt to examine if chronic oral administration of EET-A would attenuate the development of ANG II-dependent malignant hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same model, we recently showed that development of typical malignant hypertension is not simply the result of RAS overactivity, but also of its perturbed interactions with other vasoactive systems. In particular, we found that the development of ANG II-dependent malignant hypertension in Cyp1a1-Ren-2 transgenic rats is accompanied by decreased intrarenal EET concentrations [26,38,41]. Based on the above considerations, we first decided to employ the model in an attempt to examine if chronic oral administration of EET-A would attenuate the development of ANG II-dependent malignant hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…10 In contrast, the epoxyeicosatrienoic acids (EETs) produced from arachidonic acid are endothelial-derived hyperpolarizing factors that are associated with vasodilation and natriuresis 11,12 and may indirectly propagate vasodilation [13][14][15] by activating endothelial nitric oxide synthase. 16,17 EETs can be rapidly metabolized to dihydroxyeicosatrienoic acids (DHETs) by the enzyme soluble epoxide hydrolase (sEH), resulting in a concomitant loss of vasodilation. 18,19 sEH also converts the protoxins, epoxyoctadecenoic acids, to the dihydroxyoctadecenoic acids, which are potent cytotoxic and proinflammatory metabolites.…”
Section: July 2014mentioning
confidence: 99%
“…The sEH substrates, EETs, have known vasodilatory actions. [12][13][14][15][16][17][18][19]23 However, because of the short half-life of EETs, 33 these sEH substrates were below the level of detection and it was not . Schematic of proposed α-linolenic acid-induced alterations in the oxylipin profile.…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations